Counseling on the Ptsl (Complete Systematic Land Registration) Program in Central Kalijaga Village, Aikmel District, East Lombok Regency - Umami, Allan Mustafa; Al Qindy, Fatria Hikmatiar; Satriawan, Hera Alvina; Wahyuddin, Wahyuddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The majority of the people of Central Kalijaga Village work in the agricultural sector, where each head of the family owns/or controls agricultural land with varying areas, ranging from 500 M2 to 2000 M2. Based on data, there are 590 community members with a total area of 117,400 M2 (11.74 Ha). The total area referred to has not yet been registered for rights. Meanwhile, there are only 367 community members who have registered land objects that they obtained by inheritance, gift, will and sale and purchase with a total area of 10,665 M2 (1.0665 Ha). Based on the data, the achievement of land rights registration carried out by members of the Central Kalijaga Village community on land rights objects under their control has only reached 10%. There are still 90% of land rights objects whose rights have not been registered. For this reason, in order to realize guaranteed certainty of land, rights owned by members of the community, including the status of the land, the basis for obtaining land rights, who has rights to the land and third parties who are burdened. In such a situation, public awareness and knowledge will increase about the importance of registering land rights through a complete systematic land registration program (PTSL. The formulation of the problem in this research is 1. How is the PTSL (Complete Systematic Land Registration) Program implemented in Kalijaga Tengah Village, Aikmel District, Regency East Lombok? The aim of this research is to determine the implementation of the PTSL (Complete Systematic Land Registration) Program in Central Kalijaga Village, Aikmel District, East Lombok Regency. This research method uses empirical legal research methods. One of the land registration processes in Indonesia is through the complete systematic land registration program (PTSL).